Islamic Education on Quality Digital Culture Transformation in The Succes 2030 SDGs - Wulandari, Widya (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
Facing an era of disruption, there must be a program to prepare human resources with the right digital skills to face change and maximize the potential of Indonesia's digital society. Islam faces increasingly strong pressures from globalization towards the demands of digital culture. The government's efforts are focused on encouraging the achievement of goals and increasing the quality education development index in Indonesia through the SDGs until 2030. Therefore, the aim of the research is to describe Islamic education towards quality digital cultural transformation in making the SDGs 2030 a success. The method in this research uses literature studies which involves library materials such as Bappenas (Regional Development Planning Agency) data, books, journals and other internet-based information. The conclusion of this research is that technology is increasingly bringing innovation and insight into world developments which makes people proficient in its use. Islamic education efforts in maximizing digital culture aim to shape, plan, train and develop every Muslim individual to be proficient in Islamic knowledge and life experiences. So, it doesn't just focus on digital cultural transformation in making the SDGs a success in 2030. But more on how Islamic education controls, designs and encourages digital culture.